Analysis of Structural Characteristics of the HALE Joined-Wing Configuration UAV - Junlei Sun; Ye Zhou; Zhou Zhou; Zhengping Wang (International Journal of Aerospace Engineering)
This study focuses on a high-altitude long-endurance (HALE) joined-wing configuration UAV and completes a preliminary structural design based on aircraft design indices and the fundamental principles of aircraft structure design. Based on the preliminary structural design scheme and aerodynamic shape, a structural finite element model and a vortex lattice aerodynamic analysis model of the UAV are established, and the aerodynamic loads in typical states are obtained. The aerodynamic loads of the UAV are applied to a finite element model using the multipoint row method, and the structural static characteristics are obtained. The study further explores typical structural dynamic characteristics, including natural mode, static aeroelastic, flutter, and gust response characteristics. A comparison with the structural characteristics of a conventional configuration UAV with the same structural weight reveals that the HALE joined-wing configuration UAV exhibits significant advantages in structural stiffness, mode characteristics, flutter characteristics, and static aeroelastic characteristics, whereas the gust response characteristics are essentially equivalent to those of the conventional configuration. This superiority can be attributed to the reduced wingspan while providing the same lift and effective support effect of the rear wing on the front (Frt) wings, which enhances the structural stiffness of high-aspect-ratio HALE UAVs. This configuration is particularly suitable for deployment in high-subsonic HALE configurations that require close coordination with conventional tactical aircraft. By comparing with the structural characteristics of the conventional configuration UAV with equal structural weight, the paper comprehensively analyzes the structural characteristics of the HALE joined-wing configuration and obtains the advantages and disadvantages of applying the joined-wing configuration in HALE aircraft and defines the design direction, which lays a solid foundation for the engineering application in the next stage.